177. TORIPALIMAB COMBINATION WITH CHEMOTHERAPY AND SUBSEQUENT RADIATION IN PATIENTS WITH STAGE IV ESOPHAGEAL CARCINOMA，A PROSPECTIVE PHASE II STUDY (TR-EAT TRIAL). (24th September 2022) - Wang, Qifeng; Lei, Wei; Li, Baisen; Liang, Long; Wan, Gang; Lang, Jinyi; Li, Tao
Abstract: Immune checkpoint inhibitor therapy combined with chemotherapy is safe and effective in treating advanced esophageal carcinoma; however, some patients still experience tumor progression and/or metastasis in short term. Whether and when the addition of radiotherapy to immunotherapy combined with chemotherapy improves the prognosis of patients with advanced/metastatic esophageal carcinoma needs to be investigated. Patients with unresectable stage IV ESCC with oligometatsis were enrolled. The patients were treated with two cycles of toripalimab (240 mg d1, Q3w) combined with induction chemotherapy (paclitaxel 135–175 mg/m2, d1 + carboplatin AUC = 4–6, d1, Q3W), sequentially add the radiation (30–50 Gy in 15–25 fractions), SBRT for lung, liver and bone oligometasis followed by maintenance treatment with toripalimab (240 mg d1, Q3W) for 1 year. The primary objective is to evaluate the progression-free survival (PFS), and the secondary objective is objective response rate (ORR), 2-year overall survival (OS) rates, the safety and tolerability of patients to treatment, and the identification of the changes in the healthrelated quality of life of patients. Now, 23 and 22 patients were screened and enrolled. After two cycles of induction therapy, 18 patients were evaluated. The results showed complete response (CR) in 0 patients, partial response (PR) in 6, stable disease (SD) in 9 and progressive disease (PD) in 3(1/3 occured fistula). ORR was 33.3% and DCR was 83.3%. For patients with PR + SD underwent radiotherapy, 11 patients finished plan RT were evaluated. The results showed CR in 1 patient, PR in 8, SD in 2 and PD in 0. ORR was 81.8% and DCR was 100%. Most patients experienced only grade 1–2 adverse effects and laboratory abnormalities. The interim analysis showed that the sequential radiotherapy significantly improve the ORR in the initial treatment of advanced esophageal squamous cell carcinoma (ESCC) after the treatment with toripalimab combined with chemotherapy. The initial results are encouraging and the final results are to be expected.